Teacher Strategies in Navigating Curriculum Transition: From K13 to the Merdeka Curriculum in Primary Schools - Sari, Milda; Marwiyah, St.; Masruddin, Masruddin (International Journal of Asian Education, 2025)
This study evaluates the implementation of a point-based disciplinary system in fostering student character development at SMAN 7 Luwu Timur. The research examines how structured disciplinary measures shape student behavior, enhance responsibility, and promote ethical values. Data were collected over one academic year through classroom observations, structured interviews with teachers and students, and document analysis using a qualitative research design. Findings indicate that the point-based system positively influences student discipline and moral development. Teachers reported a significant decrease in behavioral infractions and a noticeable improvement in students’ ethical awareness. The system fosters accountability and self-regulation, encouraging students to take responsibility for their actions. However, several challenges persist, including inconsistencies in enforcement and limited parental involvement. Some variations in disciplinary application undermine its effectiveness, emphasizing the need for comprehensive teacher training and structured implementation guidelines. This study contributes to the growing body of literature on character education by demonstrating the effectiveness of a structured disciplinary framework in promoting positive student behavior. It highlights the importance of integrating character-building strategies with school discipline policies to create a more supportive educational environment. The findings suggest that a well-designed point-based violation system can be a powerful tool for character education when implemented consistently and equitably. For sustainability and broader applicability, future research should explore the long-term behavioral impacts of such systems and investigate their effectiveness in diverse educational settings. Policymakers and educators must collaborate to refine disciplinary approaches that balance strict enforcement with holistic character development.